Two Analytical Schemes for the Optical Soliton Solution of the (2 + 1) Hirota-Maccari System Observed in Single-Mode Fibers - Ozdemir, Neslihan; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (MDPI, 2022)
In this scientific research article, the new Kudryashov method and the tanh-coth method, which have not been applied before, are employed to construct analytical and soliton solutions of the (2+1)-dimensional Hirota-Maccari system. The (2+1)-dimensional Hirota-Maccari system is a special kind of nonlinear Schrodinger equation (NLSEs) that models the motion of isolated waves localized in a small part of space, and is used in such various fields as fiber optics telecommunication systems, nonlinear optics, plasma physics, and hydrodynamics. In addition, the Hirota-Maccari system defines the dynamical characters of femtosecond soliton pulse propagation in single-mode fibers. Analytical solutions of the model are successfully acquired with the assistance of symbolic computation utilizing these methods. Finally, 3D, 2D, and contour graphs of solutions are depicted at specific values of parameters. It is shown that the new Kudryashov method and the tanh-coth method are uncomplicated, very effective, easily applicable, reliable, and indeed vital mathematical tools in solving nonlinear models.
Keywords: new Kudryashov method; tanh-coth method; isolated waves; single-mode fiber; optic soliton; EQUATION; Astronomy & Astrophysics; Physics